Investigating university students’ attitude towards English learning and classroom activities - Đặng Thị Vân Anh (Journal of Technical Education Science, 2014)
Learners’ attitude and motivation greatly contribute to the success of a course. This article reports the result of a study on attitude and motivation of non-English majors conducted at University of Technical Education, Ho Chi Minh City. The research was to identify students’ attitude and motivation in English classes as well as their opinions on classroom activities. Findings from data collected through questionnaires for both students and English teachers are expected to help teachers and those in charge have better understanding of learners’ motivation and expectation so that proper changes in the curriculum, syllabi, textbooks, teaching methods and so on can be made to improve the quality of teaching and learning English in tertiary education.